2013
DOI: 10.1111/bjso.12021
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a group: Value convergence and emergent work group identities

Abstract: This study examines the process of group identity formation through social interaction in real-life work groups, with a focus on achievement values as content of work group identities. Extending research on social identity formation, we examined the process of value convergence as group members negotiate common group goals. Specifically, we predicted that work group members would influence each other's achievement values and that value convergence over time would underlie emergent work group identities and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…We propose that this buffering of the negative relation between relationship conflict and team identity in East Asian teams will occur at later stages of team existence, because team identity evolves over time through group member contact and communication (Meeussen, Delvaux, & Phalet, ). As such, we test that relation at later stages of team development when enough time has passed to allow for formation of team identity.…”
mentioning
confidence: 99%
“…We propose that this buffering of the negative relation between relationship conflict and team identity in East Asian teams will occur at later stages of team existence, because team identity evolves over time through group member contact and communication (Meeussen, Delvaux, & Phalet, ). As such, we test that relation at later stages of team development when enough time has passed to allow for formation of team identity.…”
mentioning
confidence: 99%
“…We found that in small groups with low levels of ethnic diversity, group members aligned their relational and achievement values over time. This corroborates previous findings of emergent group identities (Postmes et al ., , ) and value convergence in low diversity groups (Meeussen, Delvaux, et al ., ; Meeussen, Schaafsma, et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the many benefits of value fit, recent research has looked into how shared values come about in a group. Arguing from bottom‐up group processes that members can create a shared identity over time (Postmes, Baray, Haslam, Morton, & Swaab, ; Postmes, Haslam, & Swaab, ), a longitudinal study found evidence of the dynamic nature of value sharing in ethnically homogeneous groups working on a shared project (Meeussen, Delvaux, & Phalet, ). This study showed that the achievement values of group members became more similar over time.…”
Section: Introductionmentioning
confidence: 99%
“…Those who perceive they are poorly liked may reduce the unpleasant feeling by mending relationships, or if this is not practical or desired, leaving the group entirely. This behaviour is prominent for those who hold an identity linked to their group, who therefore cannot tolerate being disliked by in-group colleagues, and willingly engage in out-group exclusion [37]. Liked within organisations is considered like constructs such as social cohesion, interpersonal climate, and in the negative sense, relationship conflict [33].…”
Section: Likedmentioning
confidence: 99%